Peran Guru Fikih dalam Mempersiapkan Masa Aqil Baligh Kelas IV MI-NU 01 Kemantran - Retno Walyunita; Aini, Rofiqotul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The aqil puberty period is the boundary period between mumayyiz and mukallaf. The aim of this research is to describe the role of fiqh subject teachers in preparing for puberty for class IV students aged 9-11 years at MI NU 01 Kemantaran, to describe the results of the role of fiqh subject teachers towards class IV students aged 9-11 years in preparing to enter the puberty period, to describe the supporting and inhibiting factors for teachers of fiqh subjects in preparing for the puberty period. This research is qualitative research with the type of research, namely field research. The results of the research show that the role of fiqh teachers in preparing students for puberty is as educators and instructors, as mentors, as mentors, as role models and motivators. The results of the role of the fiqh teacher for class IV students are: awareness in performing worship, how to dress properly and knowing the prohibitions when you reach puberty. Supporting factors in preparing students for puberty are teachers, school facilities and infrastructure. Meanwhile, the inhibiting factors are parents and the lack of communication between parents and children.